Effects of climate change on plant resource allocation and herbivore interactions in a Neotropical rainforest shrub - Lauren D. Maynard; Elodie Moureau; Maaike Y. Bader; Diego Salazar; Gerhard Zotz; Susan R. Whitehead (Ecology and Evolution, 2022)
Abstract Climate change is a mounting global issue, but its consequences will be variable across regions. Tropical species are hypothesized to have reduced climatic adaptability and plasticity. Yet, relative to temperate species, less is understood about how they will respond to climate change. Rising temperature and atmospheric CO2 could impact plant–herbivore systems directly by altering species traits or abundances, or the effects could be indirect by altering the strength and direction of the relationships that govern organismal strategies and interactions. Using open‐top chambers in a Neotropical wet forest, we applied a full‐factorial combination of active warming and CO2 fertilization to investigate the above‐ground, short‐term effects of climate change on plant–herbivore interactions in a common Neotropical shrub, Piper generalense. We aimed to answer two main questions: (1) Could climate change alter plant–herbivore systems through direct effects on plant growth rate, chemical defense, and/or insect herbivore damage rate? and (2) Could climate change affect plant–herbivore systems indirectly by altering (a) the strength of plant resource allocation trade‐offs between growth and defense or (b) the effectiveness of plant chemical defense against herbivory? None of the microclimate treatments had direct effects on plant growth, chemical defense, or herbivore damage. However, we did observe a positive relationship between growth and chemical defense in treatments mimicking climate‐change conditions, which partially supports the growth–differentiation balance hypothesis. We did not detect any effects of treatments on the effectiveness of plant chemical defense against herbivory. It appears that, in this system, increased CO2 concentration and temperature may cause indirect, cascading consequences, even where direct effects are not observable. We recommend more climate‐change experiments addressing multi‐trophic interactions that focus not only on the direct responses of organisms but also on the ways in which climate change can restructure the relationships that govern complex biotic systems.